2021
DOI: 10.1094/pdis-08-20-1791-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Leaf Wilt Caused by Fusarium proliferatum and F. brachygibbosum on Date Palm (Phoenix dactylifera) in Tunisia

Abstract: Since 2017, a new leaf wilt syndrome was observed in plantations of date palm in Tunisia. Its incidence increases sharply from year to year, especially in ‘Deglet Nour’ trees, aged between 5 and 15 years. In severe cases, the large number of dried leaves per tree can lead to complete cessation of date production. Symptoms appear on one or more leaves in the center of the crown. Whitening and drying start at the top of the leaflets and proceed to their base, while the midrib remains green. Then the whole leaf d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…-Allium cepa (Tirado-Ramirez et al, 2021); -Beta vulgaris (Cao et al, 2018); -Cannabis sativa (Punja et al, 2018(Punja et al, , 2019; -Citrullus lanatus (Renter ıa-Mart ınez et al, 2015); -Citrus spp. (Al-Sadi et al, 2014); -Glycine max (Wang et al, 2021); -Nerium oleander (Mirhosseini et al, 2014); -Nicotiana tabacum (Qiu et al, 2021) -Phoenix dactylifera (Al-Sadi et al, 2012;Saleh et al, 2017;Al-Nadabi et al, 2020;Namsi et al, 2020;Nishad and Ahmed, 2020;Rabaaoui et al, 2021); -Prunus dulcis (Seidle, 2016;Stack et al, 2017); -Solanum tuberosum (Zimudzi et al, 2017;Azil et al, 2021); -Sorghum vulgare (Padwick, 1945); -Trifolium subterraneum (Tan et al 2011); -Triticum spp. (Ali et al, 2020;€ Ozer et al, 2020;Mohammed-Ameen et al, 2021;Van Coller et al, 2013); -Vitis vinifera (Akg € ul and Ahio glu, 2019); -Zea mays (Shan et al, 2017;Fallahi et al, 2019).…”
Section: Host Rangementioning
confidence: 99%
“…-Allium cepa (Tirado-Ramirez et al, 2021); -Beta vulgaris (Cao et al, 2018); -Cannabis sativa (Punja et al, 2018(Punja et al, , 2019; -Citrullus lanatus (Renter ıa-Mart ınez et al, 2015); -Citrus spp. (Al-Sadi et al, 2014); -Glycine max (Wang et al, 2021); -Nerium oleander (Mirhosseini et al, 2014); -Nicotiana tabacum (Qiu et al, 2021) -Phoenix dactylifera (Al-Sadi et al, 2012;Saleh et al, 2017;Al-Nadabi et al, 2020;Namsi et al, 2020;Nishad and Ahmed, 2020;Rabaaoui et al, 2021); -Prunus dulcis (Seidle, 2016;Stack et al, 2017); -Solanum tuberosum (Zimudzi et al, 2017;Azil et al, 2021); -Sorghum vulgare (Padwick, 1945); -Trifolium subterraneum (Tan et al 2011); -Triticum spp. (Ali et al, 2020;€ Ozer et al, 2020;Mohammed-Ameen et al, 2021;Van Coller et al, 2013); -Vitis vinifera (Akg € ul and Ahio glu, 2019); -Zea mays (Shan et al, 2017;Fallahi et al, 2019).…”
Section: Host Rangementioning
confidence: 99%
“…In this study, we report for the first time an extensive study on the Alternaria species occurring on date palm leaves showing leaf spot symptoms, in Tunisia. In recent years, a high incidence of leaf spot disease was recorded on date palm ( Namsi et al, 2021 ). In the period 2017–2019, we inspected palm date plantations located in Djerib, the most intense area of date production in Tunisia.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above mentioned species, other species have been associated with leaf blight in Tunisia. Ben Chobba et al (2013) identified also A. gaisen (included in Alternaria Section) by using ITS1 and ITS4 genes, whereas Namsi et al (2021) identified A. mali , by using ITS , gpd , CaM , and Alt-a1 genes. However, in other studies, A. mali was proposed as synonymous to A. alternata species ( Woudenberg et al, 2015 ), whereas, according to Somma et al (2019) , A. mali was phylogenetically more similar to A. gaisen , both species being distinguishable from A. alternata .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strains were grown for 7–10 days at 25 °C on PDA under a light/darkness photoperiod of 12 h. For each strain, the inoculum was prepared by flooding the agar plate surface with 10 mL of sterile distilled water (SDW) and scraping with a spatula. Conidial suspensions were filtered through four layers of cheese cloth and were diluted with SDW for obtaining a final concentration of 10 5 conidia mL −1 [ 64 ].…”
Section: Methodsmentioning
confidence: 99%